Computed Tomography Scan and ICD Interaction. (1st November 2009) - Porres, Jose M.; Cerezuela, Jose L.; Luque, Oscar; Marco, Pilar
Abstract : Although it has been considered a safe procedure, computed tomography scanning uses high doses of radiation and can cause malfunctioning in those patients with ICD when the radiation is directly incident on the device. We present a case of ventricular oversensing during a thoracic computed tomography.